SPECTRUM OF VON WILLEBRAND’S DISEASE IN PUNJAB: CLINICAL FEATURES AND TYPES - Khan, Muhammad Kaleem; Khan, Sunia Qasuria; Malik, Naumaan Aslam (Journal of Ayub Medical College Abbottabad, 2014)
Background: Von Willebrand’s disease (VWD) is a common inherited bleeding disorder caused by quantitative deficiency (Type-1 & Type-3 VWD) or qualitative defect of Von Willebrand’s Factor (Type-2 VWD). Regarding VWD limited studies are available in Pakistan. The current study was aimed to determine the clinical presentation and frequency of types of VWD. Methods: A cross sectional study was carried out from 16th December 2012 to 15th December 2013 on fifty one patients of VWD. Results: Patients were diagnosed on the basis of prolonged bleeding time, abnormal APTT, reduced level of VWF: Ag, FVIII, VWF: RCo and ratio of VWF: RCo/VWF Ag. Among them 26 (50.98%) were male and 25 (49.02%) were female. Type3 VWD (94.12%) was found to be the commonest type. Two (3.92%) cases of type-2 VWD and only one (1.96%) case of type-1 VWD were identified. Easy bruising was the most commonly observed clinical presentation, 21 (41.18%) patients, followed by epistaxis 7 (13.73%), gum bleed 4(7.84%) menorrhagia 5(9.80%), haemarthosis 2(3.92%), haematoma formation 5 (9.80%), bleeding after circumcision 2 (3.92%), bleeding after surgery 2 (3.92%) and umbilical cord bleeding 3 (5.88%). Consanguineous marriages were reported in parents of 42 (82.4%) patients. Family history of bleeding disorder was reported in 44 (86.27%) of cases. Conclusion: Type-3 VWD was found to be the commonest type which can be attributed to the fact that type-3 VWD is transmitted through autosomal recessive pattern of inheritance and consanguineous marriages are highly practiced in our society leading to high frequency of this form of VWD. Easy bruising and epistaxis were concluded to be the most common clinical presentation. Menorrhagia was found to be common in the females of child bearing age. Keywords: von Willebrand disease. Bleeding time. Ratio of VWF: RCo/VWF Ag